Bacterial Profile and Antimicrobial Susceptibility Pattern of the Isolates from Stethoscope, Thermometer, and Inanimate Surfaces of Mizan-Tepi University Teaching Hospital, Southwest Ethiopia - Teshale Worku; Dejene Derseh; Abera Kumalo (International Journal of Microbiology)
Background. Nosocomial infections occur among patients during their stay in hospitals. The severity of infection depends on the characteristics of microorganisms with a high risk of being acquired when the environment is contaminated. Antibiotic-resistant bacteria are emerging rapidly around the globe creating a serious threat. Methods. A cross-sectional study was conducted from December 2016–February 2017 at Mizan-Tepi University Teaching Hospital, Southwest Ethiopia. Samples were collected from the equipment and hospital surfaces. The isolated bacteria were checked for susceptibility by the Kirby–Bauer disc diffusion method following the standards of CLSI 2014. Health professionals and sanitary team members were included in the study which assessed the disinfection practice of objects from which samples were taken. Data were analyzed using SPSS version 20.0. Results. A total of 201 swab samples were taken, and most bacteria were recovered from thermometer and floor consisting of 21.6% S. aureus, 19.3% CoNS, 15.9% E. coli, 14.8% Klebsiella species, 11.4% P. aeruginosa, 10.2% Proteus species, and 6.8% Serratia species. The most multidrug resistant organisms were S. aureus (79%), Klebsiella species (53.8%), CoNS (47%), and Proteus species (44.4%). Only 6.45% of health professionals disinfect their stethoscope consistently. Conclusion. S. aureus, CoNS, and E. coli were the predominant isolates. Most isolates showed highest susceptibility to ciprofloxacin and least to ampicillin and penicillin. There is no regular sanitation and disinfection of hospital equipment and surfaces.